Development of a Computational Thinking (CT) Module to Help Pre-Service Teachers Learn How to Design CT Instruments - Yuniarti Suhendi, Herni; Ardiansyah, Ryan; Diella, Dea (KnE Social Sciences, 2024)
The lack of a Computational Thinking (CT) module, which teaches how to design a CT assessment instrument causes pre-service teachers to be unable to create one. This can cause students at school to not be able to measure their achievements related to CT. This study aimed to develop a CT module to support the ability of pre-service teachers to design CT assessment instruments. This research was a development study that refers to the 4-D model, but the dissemination stage was not carried out. The research subjects were 94 pre-service teachers, 70 female students and 24 male students majoring in Biology Education in semester 4 of the academic year 2021/2022. This research instrument used a validation sheet by material experts and linguists and the test item analysis sheet with 13 criteria made by the directorate of high school development in 2010. The data analysis technique used in this study is a quantitative descriptive analysis technique. The results showed that the conclusions from the validation of the modules developed from the material and presentation aspects were an average of 88.94. The language and readability aspects were an average of 80.56, and both were in the very good category. In contrast, the results of the item analysis on the material, construction and language/culture aspects had a score of 77.45%, 50.29% and 84.71%. The average percentage of ability in designing assessment instruments was 70.82%. This study concluded that the module that has been developed is suitable for use and can support the ability of pre-service teachers to design CT assessment instruments. Keywords: computational thinking, module, pre-service teachers, design, CT instruments